2020
DOI: 10.4236/ojn.2020.109058
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Chronic Heart Failure Patients

Abstract: Background: Chronic Heart Failure is a complex clinical conditions affecting patients' Quality of Life (QoL) globally. Objective: The aim of the study was to identify the factors influencing the quality of life of the chronic heart failure patients. Methods: A descriptive exploratory study was carried out by face-to-face interview with structured standard questionnaire. One hundred and forty two hospitalized chronic heart failure patients were conveniently recruited from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…A significant negative association between age and HRQoL was observed in other studies; the lower the age, the worse the quality of life 58,60 . According to the results of previous studies 16,57,69 , gender was a significant predictor of poor HRQoL, with women reporting significantly lower quality of life than men. Ahmeti et al reported that females had poorer quality of life than males with HF 38 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A significant negative association between age and HRQoL was observed in other studies; the lower the age, the worse the quality of life 58,60 . According to the results of previous studies 16,57,69 , gender was a significant predictor of poor HRQoL, with women reporting significantly lower quality of life than men. Ahmeti et al reported that females had poorer quality of life than males with HF 38 .…”
Section: Discussionmentioning
confidence: 96%
“…This finding is supported by previous studies 16,70,71 . This may be attributed to unemployed individuals often having a lower economic status and experience financial hardship due to medication and other health costs, which negatively impact management of HF and reduce their HRQoL 69 . Another factor which influenced HRQoL in people with HF was social support.…”
Section: Discussionmentioning
confidence: 99%
“…The results are also in line with a previous study that stated income is a factor that could affect the quality of life of heart failure patients. Financial difficulties, job loss, increased cost of living, and treatment negatively impact their quality of life (17). In this study, heart failure patients under treatment at this hospital were included who generally use health insurance that the Aceh Government, Indonesia, has programmed.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HF is increasing not only because of population aging but also because of improved cardiovascular disease treatment (Dunlay et al, 2021). HF is a complex clinical condition with various signs and symptoms, including poor cardiac function and physical capacity, that results in poor health-related quality of life (HRQOL; Costa et al, 2020). One study conducted across 15 countries reported patients with HF to be older and to have generally poorer physical and mental functioning, sense of coherence (SOC), and quality of life (Lu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%